Analysis of IOT in Daily Life - Sangamithra, A; Mary, Margaret J (International Journal of Computer Sciences and Engineering, 2025)
One of the major key roll concepts in today’s technology is internet of things ,IOT which plays a very major role in daily life , with the help of IOT we can make our surroundings in the automated way. IOT is the concept of machine to machine communication , all the devices can be monitored and controlled in an automated way without the human presence, In this paper we discuss about the use of IOT , various applications of IOT , security issues in IOT. This survey will be helpful for the researchers to know about the IOT as well as introducing the new techniques for implementing the IOT in different applications with more advanced way.